The Necessity of Emotion Recognition from Speech Signals for Natural and Effective Human-Robot Interaction in Society 5.0 - Ulgen Sonmez, Yesim; Varol, Asaf (Ieee, 2022)
The history of humanity has reached Industry 4.0 that aims to the integration of information technologies and especially artificial intelligence with all life-sustaining mechanisms in the 21st century, and consecutively, the transformation of Society 5.0 has begun. Society 5.0 means a smart society in which humans share life with physical robots and software robots as well as smart devices based on augmented reality. Industry 4.0 contains main structures such as the internet of things, big data analytics, digital transformation, cyber-physical systems, artificial intelligence, and business processes optimization. It is impossible to consider the machines to be without emotions and emotional intelligence within the transformation of smart tools and artificial intelligence, in addition, while it is planned to give most of the commands with voice and speaking, it became more important to develop algorithms that can detect emotions. In the smart society, new and rapid methods are needed for speech recognition, emotion recognition, and speech emotion recognition areas to maximize human-computer (HCI) or human-robot interaction (HRI) and collaboration. In this study, speech recognition and speech emotion recognition studies in robot technology are investigated and developments are revealed.
10th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 06-07, 2022 -- Maltepe, TURKEY
Keywords: speech data; speech emotion recognition; speech recognition; robots